Populism and Populist Discourse in North America - Macaulay, Marcia (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"This volume offers a significant and engaging overview of the phenomenon of populism in time and in the two countries of the United States and Canada. The focus on populism as a political discourse, both in the rhetorical sense, is one particular merit of this book helping to understand this extremely topical political phenomenon. Anyone concerned about how populist discourse works will benefit from this study." - Francesca De Cesare, University of Naples "L'Orientale", Italy This book examines the origins of populism in Canada and the United States and its development into a powerful and at times disturbing political force. Focus is on five historical periods: The Populist Party of the United States in the 1890s, Prairie Populism in Canada during the early and mid-20th century, the Reform Party of Canada in the 1980s and 90s, the 'left' and 'right' populism of Bernie Sanders and Donald Trump in the early 21st century, and the phenomenon of Ford Nation in modern day Ontario, Canada. The author extends Ernesto Laclau's analysis of populism as a 'logic' in On Populist Reason (2005) to explore how a 'people' come into being in their conflict or clash with an 'elite,' defined by Chartists in the 19th century as "idlers," providing a contrast between 'producers' and 'non-producers.' The author examines the linguistic media (speeches, books, radio, twitter, Facebook) used in populist discourse to convey a political message and to articulate the needs, wishes and will of a newly born 'people' in their numerous guises and expressions, from "the plain people," to "the little guy," or to "brothers and sisters." This volume will be of interest to researchers in an interdisciplinary range of fields, including discourse analysis, corpus linguistics, pragmatics, rhetoric and stylistics, political communication, social movements theory, media studies, and Canadian and American history. Marcia Macaulay is an Associate Professor of English and Linguistics at Glendon College, York University, Canada. Her work focusses on linguistic variation, speech act theory, stylistics, political discourse and gender and language. She is the co-editor of Pragmatics and Context (2012) and the editor of Populist Discourse: International Perspectives (Palgrave Macmillan, 2019).
Chapter 1: Introduction -- Chapter 2: The People's Party -- Chapter 3: Prairie Populism -- Chapter 4: Constructed Populism: The Reform Party of Canada -- Chapter 5: Modern American Populism: Donald Trump and Bernie Sanders -- Chapter 6: Ford Nation -- Chapter 7: Conclusion. .
Keywords: Pragmatics; Knowledge, Sociology of; Communication in politics; Applied linguistics; Language and languages-Style.; Rhetoric; America-History.; Pragmatics; Sociology of Knowledge and Discourse; Political Communication; Applied Linguistics; Rhetorics; History of the Americas